Development of biotic ligand model–based freshwater aquatic life criteria for lead following US Environmental Protection Agency guidelines. (10th July 2017) - DeForest, David K.; Santore, Robert C.; Ryan, Adam C.; Church, Brian G.; Chowdhury, M. Jasim; Brix, Kevin V.
Abstract: The US Environmental Protection Agency's (USEPA's) current ambient water quality criteria (AWQC) for lead (Pb) in freshwater were developed in 1984. The criteria are adjusted for hardness, but more recent studies have demonstrated that other parameters, especially dissolved organic carbon (DOC) and pH, have a much stronger influence on Pb bioavailability. These recent studies have been used to support development of a biotic ligand model (BLM) for Pb in freshwater, such that acute and chronic Pb toxicity can be predicted over a wide range of water chemistry conditions. Following USEPA guidelines for AWQC development and using a methodology consistent with that used by the USEPA in developing its recommended BLM‐based criteria for copper in 2007, we propose acute and chronic BLM‐based AWQC for Pb in freshwater. In addition to the application of the BLM approach that can better account for site‐specific Pb bioavailability, the toxicity data sets presented are much more robust than in 1984, and there are now sufficient chronic Pb toxicity data available that use of an acute‐to‐chronic ratio is no longer necessary. Over a range of North American surface waters with representative water chemistry conditions, proposed acute BLM‐based Pb criteria ranged from approximately 20 to 1000 μg/L and chronic BLM‐based Pb criteria ranged from approximately 0.3 to 40 μg/L. The lowest criteria were for water with low DOC (1.2 mg/L), pH (6.7), and hardness (4.3 mg/L as CaCO3), whereas the highest criteria were for water with high DOC (9.8 mg/L), pH (8.2), and hardness (288 mg/L as CaCO3 ). Environ Toxicol Chem 2017;36:2965–2973. © 2017 SETAC